Implementasi Aplikasi SP4N-LAPOR! dalam Pengelolaan Pengaduan Masyarakat di Dinas Komunikasi dan Informatika Kabupaten Tangerang - Nurhadi, Salma Putri; Purbaningrum, Dini Gandini; Nuraulia, Ridela (Ikatan Da'i Indonesia, 2023)
SP4N-REPORT! (National Public Service Complaint Management System - People's Online Aspiration and Complaint Service), which is a service for conveying all community aspirations and complaints through several complaint channels. The aim of this research is to find out an overview of the implementation of the SP4N-LAPOR Application! in managing public complaints at the Tangerang Regency Communication and Information Service which has been implemented as a public service innovation so far. The research method uses a qualitative descriptive method with an approach in the form of literature study or literature study, through a collection process obtained from various sources including journals, books, documentation, the internet and libraries. Meanwhile, the type of data in this research is secondary data, namely data obtained indirectly, namely taking data from journals related to research. The research results show that the SP4N-LAPOR Application program in providing convenience to public complaint services as access for the community in conveying aspirations, requests for information on government performance and improving the quality of public services at the Tangerang Regency Communication and Information Service has been running well. Proven through several applications by providing evaluations, collaboration with other institutions such as LSN, subscribing to big data software, and creating a special complaint management structure, with the aim of increasing responsiveness and quality in managing complaints from the public.